Residue profiles and therapeutic applications of unapproved anti-inflammatory drugs in cattle - Fritz, Bailey Renée (My University, 2025)
Disease and routine management procedures result in cattle regularly experiencing pain, inflammation, or stress. The ‘Five Domains’ animal welfare paradigm establishes that animals should have freedom from pain, injury, and disease and freedom to express normal behaviors. Effectively managing pain and inflammation due to disease and management procedures can meet these basic welfare needs. Non-steroidal anti-inflammatory drugs and glucocorticoids are commonly used to treat pain, inflammation, and stress. Because there are few approved anti-inflammatory drug options for cattle in the United States, veterinarians must use drugs in an extra-label manner in certain situations. However, for extra-label drug use (ELDU) to be legal, veterinarians must determine a conservative withdrawal interval (WDI) to avoid violative residues in edible tissues and ensure the treated animal does not enter the food chain prior to the end of that period. Variability in animal populations – whether due to age, breed, physiologic status, or disease state—can alter the pharmacokinetics of drugs. Thus, it is prudent to generate data to enable estimation of WDI for drugs in healthy populations and those of interest for a particular drug regimen. Industrial hemp (IH) is being evaluated in cattle as a novel, sustainable feed source and for possible therapeutic applications. Inclusion of IH in cattle feed or as a drug is currently illegal, in part due to concerns over the transfer of cannabinoids into edible tissues. However, data supporting tissue cannabinoid concentrations and therapeutic effects of IH are of interest to both promote and inform its approval as a feed ingredient. This dissertation begins with a review of unapproved anti-inflammatory drugs pharmacokinetics and current IH research in cattle. Further chapters discuss residue depletion profiles for salicylic acid in milk following aspirin treatment in cows and for cannabinoids in tissues following IH administration in steers. Additional pharmacodynamic and pharmacokinetic considerations for IH in cattle are explored through (1) evaluation of the effects of IH and repeated transportation events on measures of stress and inflammation and (2) description of the plasma cannabinoid profile after long-term IH administration. Salicylic acid was detected in the milk and WDI were estimated for treated cows. Results indicated that a 120 h to 156 h WDI may be appropriate; this is longer than the previous 24-hour recommendation. Following aspirin administration, prostaglandin production was reduced for up to 12 h. When this aspirin report was initially published, extra-label aspirin use was common in dairy cattle and the FDA used enforcement discretion in not pursuing action against administration of unapproved, over-the-counter marketed products. However, concerns with mass aspirin treatment of dairy cows during the highly pathogenic avian influenza outbreak have since prompted prohibition of extra-label aspirin use. Following administration of IH inflorescence to Holstein steers, a variety of cannabinoids, including the psychoactive [Delta]9-tetrahydrocannabinol (9-THC) and the bioactive cannabidiol (CBD), were detected in tissues. Both CBD and 9-THC accumulated in adipose tissue. Slow depletion of some cannabinoids resulted in WDI estimates with a large degree of extrapolation. Exposure estimates for human consumers demonstrated that a single demographic (newborns) exceeded the most conservative international toxicity threshold for 9-THC. Additional research should establish safe thresholds of cannabinoids in younger (vulnerable) demographics. Results showed that IH administration, in a complex relationship with transportation and time, may reduce prostaglandin E2 metabolites (a measure of inflammation). Transported cattle had increased activity during transportation. However, both transported and non-transported cattle lay down more following the return of the transported group. Transport elicited changes in blood parameters and cortisol that are consistent with previous reports. These data will enable the design of impactful future studies regarding IH use in cattle. During long-term IH administration, predominantly acidic cannabinoids were detected in plasma. (−)-7-nor-7-carboxy cannabidiol (CBD-7-acid) reached the highest concentrations and depleted the most slowly after cessation of IH administration. A handful of cannabinoids, including CBD-7-acid, were detected in cattle not receiving IH. This suggests that cattle not receiving IH could have detectable cannabinoid concentrations in the blood if cohoused with animals that are exposed to IH. In conclusion, our results provided information for generation of WDI following administration of aspirin to lactating cows. Our data provide information on target tissues and marker residues for post-slaughter surveillance and a suggest a promising candidate for ante-mortem testing of IH exposure. Treatment with IH may reduce some inflammatory markers. Further work should continue to evaluate the food safety profile of cattle exposed to IH as well as the potential therapeutic benefits of IH administration.
Keywords: Anti-inflammatory; Aspirin; Industrial hemp; Residue; Transportation; Withdrawal interval